Exploring the Policy of relinquishing Judicial Powers to the Jurists in Determining Islamic Banking Disputes: The Case of Bank Negara's Shariah Advisory Council - Shuaib, Farid Sufian (2011)
Islamic banking and finance is identified as one of the areas that may contribute to economic transformation for Malaysia. Malaysia is targeted to be the hub for Islamic banking services and education. The country has to keep up with a fast developing Islamic banking sector by providing adequate regulatory framework. One of the elements in this framework is dispute resolution mechanism. A peculiar policy adopted by the government in regulating Islamic banking is by requiring the courts to refer to an advisory committee to make a final decision on disputes regarding Islamic banking and finance. This is peculiar since the courts are usually the final arbiter of disputes including matters involving banking and finance. This policy is evidenced in the new Act of the Central Bank of Malaysia Act 2009 replacing the Central Bank of Malaysia Act 1958. The new Act requires the courts to refer to the Shariah Advisory Council on matters of Islamic banking and the decision of the Council is binding on the courts. Eight out of eleven members of the Council are Islamic banking scholars and jurists. This paper seeks to explore the possible reasons for such divergent route adopted by the new Act and to consider advantages and disadvantages by relegating the final arbiter of disputes to jurists rather than judges.